Ab Initio Study on the Stability of NgnBe2N2, NgnBe3N2 and NgBeSiN2 Clusters1. Issue 12 (30th May 2014) - Pan, Sudip; Moreno, Diego; Cabellos, José Luis; Merino, Gabriel; Chattaraj, Pratim K.
Abstract The global minima of Be2N2, Be3N2 and BeSiN2 clusters are identified using a modified stochastic kick methodology. The structure, stability and bonding nature of these clusters bound to noble gas (Ng) atoms are studied at the MP2/def2‐QZVPPD level of theory. Positive BeNg bond dissociation energy, which gradually increases down Group 18 from He to Rn, indicates the bound nature of Ng atoms. All of the Ng‐binding processes are exothermic in nature. The Xe and Rn binding to Be2N2 and Be3N2 clusters and ArRn binding to BeSiN2 are exergonic processes at room temperature; however, for the lighter Ng atoms, lower temperatures are needed. Natural population analysis, Wiberg bond index computations, electron density analysis, and energy decomposition analysis are performed to better understand the nature of BeNg bonds.